A powder preparation kit from the Middle Bronze Age at Megiddo, Israel: Tools and raw materials. (October 2018) - Hunt, Logan; Martin, Mario A.S.; Finkelstein, Israel; Weiner, Steve
Abstract: A unique assemblage of tools dating to the Middle Bronze Age was uncovered at Megiddo (Israel). The assemblage included pestles, pounding stones, many worked stones and various colored materials. We used mainly Fourier Transform Infrared Spectroscopy (FTIR) in order to identify the bulk materials of the artifacts, as well as the materials adhering to the surfaces of the artifacts. An unusual kaolinite, quartz, calcite and hematite containing compound was used for producing red powder, charcoal for black powder and chalk, shells and bone for white powders. We conclude that the assemblage was a kit used to produce relatively small amounts of colored powders. The possible uses of the kit are discussed, including for decoration of intramural burials found in the immediate vicinity. Highlights: Report a unique in situ assemblage of over 50 artifacts from the Middle Bronze Age Most of the artifacts are clearly related to crushing and grinding activities. Four differently colored raw materials were also found in the assemblage. FTIR was used to identify the bulk materials, the raw materials and adhering materials. The assemblage was used for preparing powders of differently colored materials.